Case Report: Trauma group therapy with karate-do for war-traumatized children and adolescents - Montenegro, Mirjam Straub Ortiz; Montenegro, Patricio Ortiz; Voegeli, Fabian (Frontiers in Psychology, 2024)
Abstract Background: From the viewpoint of health and education, traumatized children and adolescents who have fled from war and conflict zones to Switzerland represent a high-risk group, as they suffer from psychiatric symptoms to an above-average extent and on several levels: somatic, psychological, psychosomatic, and psychosocial. Objectives: The complexity and severity of these problems overwhelm the existing school structures in many cases: There is a clear need for psychotherapeutic interventions here that goes beyond purely verbal conversational therapy and provides an holistic concept. Methodes: We propose the following novel approach: “Trauma group therapy with karate-do for war-traumatised children and adolescents” which integrates and applies the evidence-based methods of integrative Budo-Therapy, trauma-focused Cognitive Behavioral Therapy (TF-CBT), Narrative Exposure Therapy (NET) and Integrative Gestalt Therapy according to Dr. Hilarion Petzold (EAG-FPI) and validated it in a group of approximately 12 children from war and conflict zones who attend the public schools of the city of Zürich. Results: Qualitative feedback received from the teachers is promising. They report that it is now better possible for the children who go to ouer “Trauma group therapy with karate-do for war-traumatised children and adolescents” to concentrate at school and also to better regulate their feelings. Conclusion: Ouer approach seems to be a promising intervention for traumatized children and adolecents. Though it needs further evaluation.